Bioactivity-guided isolation of neuritogenic triterpenoids from the leaves of Ilex latifolia Thunb. Issue 10 (22nd September 2017) - Cao, Xueli; Liu, Yu; Li, Jing; Xiang, Lan; Osada, Hiroyuki; Qi, Jianhua
Abstract : The new triterpenoid isolated from the leaves of Ilex latifolia Thunb showed neuritogenic and antioxidative activities in vitro . Abstract : Ilex latifolia Thunb is a traditional Chinese tea and herbal medicine. In this study, one new triterpene saponin (1 ) and six known triterpenoids (2–7 ) were isolated from the methanol extract of I. latifolia using a PC12 cell bioassay system. The structures and stereochemistry of these compounds were elucidated using spectroscopic methods and chemical derivatization. This new triterpene saponin (1 ) was characterized as an ursolic type acid with a 19α-hydroxyl and a trisaccharide moiety at C-3. Compound1 significantly promoted the neurite outgrowth in PC12 cells by 52% at 10 μM, whereas compounds2–7 showed less neuritogenic activity. Structure activity relationship studies indicated that introducing a trisaccharide moiety at C-3 is important for the neuritogenic activity, but the sugar group at C-28 decreased this activity. In addition, compound1 increased the neurite outgrowth length in primary cortical neuron cells of mice and also exhibited a neuronal protection effect on H2 O2 -damaged PC12 cells at optimum concentrations.